The ups and downs of temporal orienting: a review of auditory temporal orienting studies and a model associating the heterogeneous findings on the auditory N1 with opposite effects of attention and prediction - Lange, Kathrin (Frontiers in Human Neuroscience, 2013)
The temporal orienting of attention refers to the process of focusing (neural) resources on a particular time point in order to boost the processing of and the responding to sensory events. Temporal attention is manipulated by varying the task-relevance of events at different time points or by inducing expectations that an event occurs at a particular time point. Notably, the electrophysiological correlates of these manipulations at early processing stages are not identical: Auditory studies operationalizing temporal attention through task-relevance consistently found enhancements of early, sensory processing, as shown in the N1 component of the auditory event-related potential (ERP). By contrast, previous work on temporal orienting based on expectations showed mixed results: early, sensory processing was either enhanced or attenuated or not affected at all. In the present work, I will review existing findings on temporal orienting with a special focus on the auditory modality and present a working model to reconcile the previously heterogeneous results. Specifically, I will suggest that when expectations are used to manipulate attention, this will lead both to an orienting of attention and to the generation of precise predictions about the upcoming event. Attention and prediction are assumed to have opposite effects on early auditory processing, with temporal attention increasing and temporal predictions decreasing the associated ERP correlate, the auditory N1. The heterogeneous findings of studies manipulating temporal orienting by inducing expectations may thus be the consequence of differences in the relative contribution of attention and prediction processes. The model’s predictions will be discussed in the context of a functional interpretation of the auditory N1 as an attention call signal, as presented in a recent model on auditory processing.